Review of Bremer and Haneke's "Zeugen für Gott. Glauben in kommunistischer Zeit." - Simon, Gerhard (Occasional papers on religion in Eastern Europe, 2016)
Zeugen für Gott. Glauben in kommunistischer Zeit., 2 vols. Edited by Thomas Bremer and Burkhard Haneke. Münster: Aschendorf Verlag, 2014- 2015. 276 pp. and 286 pp. respectively. ISBN 340213070 and 340213084 respectively.